Implementation of Restorative Justice in the Police in Realizing a Just Legal State - Fiesta Aulia Rizka (Universitas Negeri Semarang, 2024)
The upholding of justice, as well as usefulness and certainty of the law are the fundamental goals of the law that was created. However, in thiscase it also turns out that in reality it is difficult to realize it together. The police have an active role and participate in enforcing the law in Indonesia, especially regarding matters the might damage Indonesian public order. Restorative justice ha the main aim of seeking justice in it, namely by focusing on peace efforts by prioritizing return or restoration to the initial overall state. Restorative justice this is to restore a situation to b e better in people's lives, not to take revenge for a crime or crime committed. With the existence of restortive justice, it is hoped that it wil be able to create a just legal state as mandated by the Indonesian Constitution.